BETWEEN THE PSYCHOLOGY AND PEDAGOGY: REFLECTIONS ON CHILD DEVELOPMENT AND KNOWLEDGE SCHOOL IN THE LIGHT OF CULTURAL HISTORICAL THEORY - Barbosa, Eliza Maria [UNESP]; Silva, Janaina Cassiano (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
We analyze in this work, the aspects that characterize the relationship with Pedagogy and Psychology of Education, especially the relationship between human development and learning explained by psychogenic theory. We performed a critical analysis of this relationship based on the contributions of cultural-historical theory. We demonstrate that from some precepts, psychogenic theory establishes a model of education that takes the development of cognitive processes as basic content for educational, considering that successful transmission of knowledge to children depends primarily on the existence of schemes assimilation inherent in the activity of the subject. However, guided by Cultural-Historical theory we reaffirm an understanding of child as an individual who needs learn and grow in a world of objects, people and places of knowledge holders. So it should be considered the expansion of cultural knowledge and human produced engendered by the school pedagogical actions. The more knowledge children master greatest power over the processes that determine their lives and their conditions of existence in the social reality. That is, through the appropriation of culturally engendered processes (for education), in the course of life children acquire the properties and truly human faculties.
Keywords: Psychology of education; Psychogenetic; Cultural-Historical Theory; Early childhood education